Prevalence of avascular necrosis of femoral head in patients with cirrhosis of liver - Mahajan, Sanjeev; Gadi, Daksh; Gupta, Rahul; Sharma, Anirudh; Thind, Premjeet Singh; Gupta, Som; Kaur, Raminder (International Journal of Medicine, 2016)
Background: Amongst the multiple etiologies implicated in the development of Avascular necrosis of the femoral head, literature regarding the association of cirrhosis of liver with osteonecrosis of femoral head is scanty and is correspondingly less studied. Considering a large number of patients with liver cirrhosis in this region of our country, this study was conducted to evaluate the association of cirrhosis as an independent risk factor in the development of osteonecrosis. To the best of our knowledge No such study has been done evaluating the same in this region.Methods: This prospective analysis aimed to determine the prevalence of osteonecrosis of femoral head in patients with cirrhosis of liver, patients presenting to the hospital with established cirrhosis, diagnosed with help of ultrasonography , were evaluated for the occurance of Avascular necrosis of the femoral head.Results: The prevalence of osteonecrosis of femoral head in patients with cirrhosis of liver was evaluated to be 1.2% in the present study. Amongst this cirrhotic subgroup, the prevalence of osteonecrosis of femoral head in cirrhotic patients due to excessive alcohol consumption was calculated to be 1.1% and that of the cirrhotic patients independent of alcohol consumption came out to be 1.4%.Conclusion: Analysis of the results of the present study establishes cirrhosis of liver, the cause of which could be independent or related to alcohol consumption, as a risk factor for the development of osteonecrosis of femoral head. Significance of alcohol related cirrhosis resulting in AVN of the femoral head, though, is challenged by the present study.